Analysis Use of Fixed Assets Depreciation Method on Company Profits, - Rina Indrayani (STIE Binaniaga, 2018)
This study was conducted with the aim to know the accounting policy ofdepreciation of fixed assets determined by the company and how the influence ofaccounting policy depreciation of fixed assets applied by the company to thecompany's earnings. The research method used is descriptive method of analysis isa research that aims to collect data that have a relationship with the problemsstudied, then processed and analyzed and then the solution. While the data used isquantitative data in the form of numbers. After examining and analyzing thecompany's treatment in calculating depreciation for fixed assets, it can beconcluded that the accounting policy of depreciation of fixed assets applied by thecompany has been in accordance with the applicable financial accountingstandards that is straight-line method and the use of different methods will result indifferent amounts of depreciation. Using the straight-line method of depreciationexpense for each fixed period, profits generated in the early years are greater thanin subsequent years. While in the method of balance decreased multiplydepreciation expense higher in the early years and lower load in the coming period.The resulting profits were smaller in the early years and were greater in previousyears.